The Impact of Mandatory IFRS Adoption on Audit Fees: Theory and Evidence - Kim, Jeong-Bon; Liu, Xiaohong; Zheng, Liu (The Accounting Review, 2012)
ABSTRACT: This study examines the impact of International Financial Reporting Standards (IFRS) adoption on audit fees. We first build an analytical audit fee model to analyze the impact on audit fees for the change in both audit complexity and financial reporting quality brought about by IFRS adoption. We then test the model's predictions using audit fee data from European Union countries that mandated IFRS adoption in 2005. We find that mandatory IFRS adoption has led to an increase in audit fees. We also find that the IFRS-related audit fee premium increases with the increase in audit complexity brought about by IFRS adoption, and decreases with the improvement in financial reporting quality arising from IFRS adoption. Finally, we find some evidence that the IFRS-related audit fee premium is lower in countries with stronger legal regimes. Our results are robust to a variety of sensitivity checks. Data availability: Data are available from public sources identified in the paper.